Tambayayong ang bayanihan sa kasaysayan at kalinangang Pilipino - Abaya-Ulindang, Faina; Villan, Vicente (ADHIKA ng Pilipinas, Inc., 2020)
Philippines history and culture on mutual cooperation among Filipinos; papers of a conference.